SUPLEMENTATION OF KEMBANG TELANG (Clitoria ternatea) FOR IMPROVING THE QUALITY OF BANANA STEMS SILAGE - Suarna, I W.; Mudita, I M.; Wirawan, I W.; Suryani, N. N. (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak, 2020)
Provision of continuous and quality feed is very important to increase livestock productivity. Abundant and inexpensive available banana stems can be improved as a source of quality feed through silage technology with the addition of C. ternatea. This study combines banana stems with C. ternatea made in the form of complete feed selase by adding pollar, molasis and EM4. There are four treatments i.a. Control (Treatment A): 65% banana stems + 30% pollar + 5% (molasis + EM4); Treatment B: 55% banana stems + 10% C. ternatea + 30% pollar + 5% (molasis + EM4); Treatment C: 45% banana stems + 20% C. ternatea + 30% pollar + 5% (molasis + EM4); and Treatment D: 35% banana stems + 30% C. ternatea + 30% pollar + 5% (molasis + EM4). Each treatment consisted of three replications. The study was conducted to get the best combination of banana stem silage and C. ternatea through observations of physical quality, physical properties, nutrient content and digestibility in vitro. The data obtained were analyzed using Anova. The results showed an increase in nutrient content, digestibility of dry matter and organic matter as well as a decrease in digestive inhibiting components in vitro. The conclusion of this research is, the addition of C. ternatea in silage of banana stems up to 30% produces organic matter content, crude protein, energy, digestibility of dry matter and the highest organic matter and the lowest crude fiber content. Keywords: silage, banana stems, Clitoria ternatea, in vitro